What's right with you : an interactive character development guide - Schiering, Marjorie S., 1943- (London ; New York : Rowman & Littlefield International, 2017)
The underlining theme of this book by Marjorie Schiering is being/becoming a person of good character, and how to teach character education in the classroom, the workplace, or the home. The author clearly outlines the steps one needs to take to establish an effective character education program and offers step-by-step procedures for leading training workshops to accomplish this goal.
Includes bibliographical references (pages 173-178).
Keywords: Personality development; Character; Character; Personality development